Implementasi Nilai-Nilai Bhineka Tunggal Ika Pada Mahasiswa Angkatan 2022 Prodi PPKn UNIPA Surabaya - Suyono Suyono (International Forum of Researchers and Lecturers, 2023)
Bhineka Tunggal Ika is one of the four pillars of Indonesian nationalism, a reminder that diversity is a source of strength and wealth for the nation, and must be preserved. The values of Bhineka Tunggal Ika are important to maintain social harmony and unity. The purpose of writing this article is to observe the implementation of Bhineka Tunggal Ika values in college schools. The research subjects were students of the Class of 2022 of the PPKn study program at Unipa Surabaya. This research aims to explore and apply the values of Bhineka Tunggal Ika to students as an effort to strengthen harmony and diversity in the college environment. Bhineka Tunggal Ika, which means